Moengo on strike: The Politics of Labour in Suriname’s Bauxite Industry - Koning, Anouk de (European Review of Latin American and Caribbean Studies, 2011)
This article examines one crucial moment of contestation in colonial Suriname, the years 1941- 42, when sustained labour unrest in bauxite town Moengo led to the founding of the first mining unions. It argues that these strikes laid the groundwork for future relations between labour, company and the state and explores the kinds of socio-political alliances that were forged between labour and nationalist politicians on the one hand, and government and transnational company on the other, thereby situating this particular contestation in a larger struggle over a colonial system that aligned itself with metropolitan economic interests.Resumen: Moengo en huelga: Políticas Laborales en la Industria de la Bauxita en SurinameEn este artículo se aborda un momento crucial de la impugnación en el Suriname colonial entre los años 1941-42, cuando un persistente malestar entre los trabajadores del pueblo de la bauxita de Moengo condujo a la fundación de los primeros sindicatos mineros. Se sostiene que esas huelgas sentaron las bases de las futuras relaciones entre el trabajo, las compañías y el estado y se exploran los tipos de alianzas socio-políticas que se forjaron entre políticos laboristas y nacionalistas por un lado, y el gobierno y compañías transnacionales por el otro, situando por ello esta particular impugnación en una lucha de mayor alcance contra un sistema colonial que se identificaba a sí mismo con los intereses económicos metropolitanos.